Essays on Enviromental and Development Economics - Barros , Pedro Henrique Batista de (2019)
This dissertation is composed of two essays on environmental and development economics. The first aims to understand how economic development affected deforestation in the Brazilian Amazon from 2000 to 2015, using an Environmental Kuznets Curve (EKC). We analyzed and controlled the presence of spatial and temporal dependence with ESDA and Dynamic Spatial Panel methodologies. For the EKC model, despite obtaining an inverted "U" format, the majority of municipalities in Amazon are far below the turning point. Therefore, economic development may act as a deforestation inductor in the following decades. We confirmed the importance of the spatial-temporal components, which explains the spatial spillovers and agglomeration along with temporal inertia for deforestation. In addition, cattle herd growth along with rural credit, sugarcane productivity, extraction of wood and scale effects from agricultural sector are statistical significant, acting as environmental degraders. On the other hand, we have the productivity gains on soy and maize that inhibit deforestation. We also highlight the importance of considering land use dynamics and cross-agricultural activities leakages in policies targeting deforestation, since crops indirectly affect environmental degradation in Amazon by shifting cattle production to agricultural frontier regions, where it increase deforestation. The second essay investigates the relationship between socioeconomic development and deforestation in the Cerrado biome, with special focus on the current Brazilian agricultural frontier, known as Matopiba, using the Environmental Kuznets Curve approach. In addition, we seek to contribute methodologically to the EKC estimation, incorporating several advances not yet adopted at the same time in the specialized literature. i) The creation of a Socioeconomic Development Index to replace per capita income as a proxy for economic development; ii) the omitted-variable bias problem consideration, especially from spatial spillovers; iii) and the adoption of spatial regimes to control heterogeneity. In the spatial EKC model, we get an inverted U-shaped curve relationship between development and deforestation for both regimes. After considering indirect spatial effects, we identified that more than 50% of Matopiba and 30% of Cerrado municipalities are lower than the maximum turning point, which highlights environmental concerns, since economic growth could boost degradation. The roads expansion and cattle herd are an important deforestation inductor for both regimes while crop area has considerable indirect effects by displacing cattle to agricultural frontier regions, in addition to directly affecting Matopiba. We also identified positive spatial spillovers from forest conversion. Demographic density, agriculture GDP, crop area, soil suitability, presence of federal reserve, soybean productivity and spillovers from cattle herd, crop area and sugarcane productivity, all presented diverse statistical significance according to the regime. Heterogeneity, spatial interactions and displacements effects present in Cerrado are important to understand the biome deforestation and can help policymaking design by considering possible different outcomes.